The Impact of the IELTS Speaking Test on Teaching Methods and Test Preparation Strategies in China (International Journal of Language, Literacy and Translation, 2025)
The increasing popularity of the IELTS test preparation course in China has sparked a discussion about the level of knowledge among instructors in terms of language assessment literacy and their selected teaching methods approach. The primary objective of this study is to gain insights into the intended test evaluation goals by Chinese IELTS speaking test teachers and how it influences their selection of teaching methods. For this study, 32 Chinese IELTS speaking test teachers were invited to participate in the research. The findings indicate that teachers demonstrated a relatively satisfactory understanding of the IELTS speaking test design. However, there were differing opinions among teachers regarding the test criteria, particularly in regard to the absence of explicit mention of skills in the test materials. Moreover, the findings of the present study revealed a link between how teachers perceived the design of the target test and their support for two instructional strategies that they believed could facilitate students' learning of the abilities that will be evaluated in the actual test. The findings of this study offer valuable insights to educators, curriculum developers, and policymakers involved in IELTS, particularly regarding the significance of gathering teachers' perspectives on the goals of the target test. This study specifically highlights how vital it is to prepare teachers in language assessment literacy. Providing teachers with knowledge about testing allows them to make informed decisions and utilise more effective pedagogical practices. Through a thorough examination of test preparation in the Chinese context, the study could not only provide practical recommendations for enhancing IELTS instructional practices, but also contribute valuable insights to broader discussions surrounding the relationship between high stakes testing and teachers' pedagogical approaches.